A relação entre competências e empreendedorismo em empresas de base tecnológica - Santos, Ana Clarissa Matte Zanardo dos (Universidade do Vale do Rio do Sinos)
This study aims to analyze entrepreneurs’ individual competencies and technology-based company organizational competencies at UNITEC - an incubator in São Leopoldo, Rio Grande do Sul, Brazil – identifying how the articulation among them is processed and the impact it has on organizational practices. One of the alternatives seeking to minimize the negative effect of companies’ high death rate in their first year of life is the study of entrepreneurship as a way to favor economic development through the generation of jobs as well as through the attention to the management of competencies aiming at identifying entrepreneurial competencies that have to be worked on and articulated to encourage innovation and make technological development possible, guaranteeing the survival of technologically-based organizations. Three incubated companies, all in operation for 4 years or more, have been analyzed; the entrepreneurs, one collaborator and the incubator administrator have been interviewed in each one of them, totalin
Keywords: empreendedorismo; gestão de competências; incubadora tecnológica; competency management; entrepreneurship; technological incubator; Ciências Sociais Aplicadas